ANALISA PERHITUNGAN STRUKTUR JEMBATAN PRATEGANG (OVERPASS) PADA PROYEK TOL BALIKPAPAN – SAMARINDA (STA 65+500) - STIANDIKA, MUHAMMAD WAHYUDI (KURVA S JURNAL MAHASISWA, 2018)
The road to the palm oil plantation and the kendang ayam at the intersection of the BalSam (Balikpapan-Samarinda) STA 65 + 500 toll road, is the only access road that is the route for the delivery of plantation products and the results of chicken livestock from that location to the highway. Therefore, the government has provided a solution by creating an overpass bridge that is designed using a concrete slab construction with a support pole in the middle. The prestressed concrete method is concrete that is emphasized first through the stressing process before being loaded. It turns out that the technique is quite effective, because in addition to concrete it can carry a bigger load than before and can reduce its own weight and size of the cross section. This is clearly very beneficial for the construction world, because the volume of material can be reduced so that the weight of the profile becomes lighter and the load of the upper structure which is borne to the foundation also becomes smaller. Therefore, the authors are interested in modifying the Overpass bridge at the intersection of the Bal-Sam (Balikpapan-Samarinda) STA 65 + 500 toll road, whose initial design used concrete slab construction with one supporting pole in the center, to be a concrete slab construction without a supporting pole replaced by the